The effect of weed control using herbicide on soil bacteria, growth, and yield of sweet corn - Bayyinah, Lafi Na'imatul; Purwanto, Purwanto; Syarifah, Risqa Naila Khusna; Pratama, Rama Adi; Widiyawati, Ida; Hendra, Hendra (Universitas Padjadjaran, 2025)
Weeds are managed by herbicides, but this can reduce the abundance of soil bacteria. This research aimed to determine the effect of active compounds of herbicides on weeds, the abundance of soil bacteria, growth and yield of sweet corn. The experiment was conducted from June to October 2023 in the fields and Laboratory of Agronomy and Horticulture, Universitas Jenderal Soedirman, Purwokerto. A randomized block design was used, consisting of eight treatments and four replications. The treatments included control (H0); weeding (H1); paraquat (H2); glyphosate (H3); paraquat, atrazine, mesotrione (H4); glyphosate, atrazine, mesotrione (H5); paraquat, atrazine, mesotrione, nicosulfuron (H6); and glyphosate, atrazine, mesotrione, nicosulfuron (H7). Results showed that glyphosate and paraquat, were applied before planting, could suppress weeds on sweet corn until 15 days after planting (DAP). Application of atrazine, mesotrione, and nicosulfuron at 21 DAP can increase the success of weed control observed up to 35 DAP of sweet corn. The application of glyphosate, atrazine, and mesotrione showed the highest values for growth variables (plant height, number, and leaf greenness index) and yield variables (fresh weight, diameter, and length of sweet corn cob). Herbicide decrease abundance of soil bacteria on sweet corn field, from 10.07x10-8 CFU/mL to 9.55x10-8 CFU/mL (total bacteria), 9.53x10-8 CFU/mL to 9.52x10-8 CFU/mL (phosphate solubilizing bacteria), 9.90x10-8 CFU/mL to 9.40x10-8 CFU/mL (Rhizobium) and 9.91x10-8 CFU/mL became 9.78x10-8 CFU/mL (nitrogen fixing bacteria). The total density of phosphate-solubilizing bacteria and nitrogen-fixing bacteria in the application of glyphosate, atrazine, and mesotrione (7.78 CFU/g and 9.52 CFU/g) was greater than control (8.77 CFU/g and 8.15 CFU/g).